2017
DOI: 10.3844/ajbbsp.2017.15.26
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Fatty Acids Profile Analyses of Commonly Consumed Fresh Water Fish Species in Pakistan

Abstract: The aim of this study is to evaluate nutritional value of selected commonly consumed fresh water fish species of Pakistan. Proximate composition and fatty acids profile of mostly consumed fresh water fish species of Pakistan namely Balm or Baam (Anguilla anguilla), Sole (Channa marulius), Damra (Labeo rohita) and Malhi (Wallago atto) were analysed. Proximate composition data showed a significant difference (p<0.05) among the nutritional components except carbohydrate and gross energy contents. Protein and mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…The authors demonstrated a consistent, high-quality lipid content in terms of nutritional value, which is important for product quality in this fish, which offers tasty and attractive products with a high content of high-quality fats. The n-3/n-6 ratio in eels in local fish markets (Pakistan) was less than one, whereas the sum of EPA and DHA was 1.755 [81]. These results are not accordance with those present in the fish examined (Table 5).…”
Section: Health Riskmentioning
confidence: 63%
“…The authors demonstrated a consistent, high-quality lipid content in terms of nutritional value, which is important for product quality in this fish, which offers tasty and attractive products with a high content of high-quality fats. The n-3/n-6 ratio in eels in local fish markets (Pakistan) was less than one, whereas the sum of EPA and DHA was 1.755 [81]. These results are not accordance with those present in the fish examined (Table 5).…”
Section: Health Riskmentioning
confidence: 63%